Eight Great American Tales - Henry, O.; Illustrated by Jamel Akib (New York Oxford University Press, 2019)
What does a poor young woman do when she loses her boyfriend or wants to find one? What little lies do we tell to make ourselves look better in the eyes of those that we love? How can a friend save someone who is sure that they are going to die? What happens when someone s clever plans all go wrong? These sweetly surprising short stories - about both good times and bad - are sometimes sad, and sometimes funny. But all of them are sure to make you think
Include Color Illustrations
Keywords: Short stories -- Manners and customs -- United States